Execution of the Occupational Safety and Health Act (1994) in the Construction Industry from Contractors’ Point of View - Awang, H.; Kamil, I.M. (EDP Sciences, 2014)
Construction is one of the highest contributing industries to occupational accidents by sector in Malaysia. Statistics have been drawn from year to year that show an increasing number of cases of accidents by industry sector. While it is impossible to completely eliminate all accidents, with a proper and effective safety and health policy or rules set by top management, especially contractors, the rate of accidents on construction sites can be reduced. The main objective of this study is to analyse the degree of application of the Occupational Safety and Health Act 1994 (OSHA 1994) in the construction industry and to identify the contributing factors leading to a lack of execution of OSHA 1994 on construction sites with a primary focus on contractors’ point of view. Five on-going construction projects in Perak were selected as case studies and site inspections were conducted. The results showed that none of the contractors have fully implemented the rules and regulations provided by the government. Within this report, some recommendations are made towards enhancing the safety and health issues on construction sites.